IMPLEMENTATION OF P5 PROJECT TO INSTILL INDEPENDENT, CREATIVE AND COOPERATION CHARACTER VALUES IN KINDERGARTEN - Yuyun Putri Mandasari; Siti Nafi'yah; Jenny Ika Misela (Suluh Adiluhung Publisher (SAPub), 2024)
Implementation of the Student Pancasila Profile Strengthening Project (P5) was to instill independent, creative, and cooperation character values in 4 kindergartens of Kediri City. This research aims to analyze the implementation of the Project (P5) including design, and management of P5. This research used a descriptive qualitative method at 4 kindergartens of Kediri City in 2022. Data collection techniques included interviews, observations, and documentation. The data was analyzed using an interactive technique, including data collection, data condensation, data presentation, and conclusion/verification. The results of the study showed that 1) the design of P5 consists of forming a team, identifying school readiness, determining the dimensions of the Pancasila Student Profile character to be strengthened, determining the theme, planning the timeline, flow, assessment, and module creation; 2) the management of P5 includes provocation and contextualization, P5 actions, and celebrating learning outcomes. P5 consist of strengthening character and continuing good habits at kindergartens. Through P5 actions, students must continue to be developed so that the cultivation of independent, creative, and cooperation character values can run optimally.